PENGINVENTARISAN KEARIFAN LOKAL DALAM PRAKTIK WANATANI KOPI DALAM DEBAT KELESTARIAN FUNGSI HIDRO-OROLOGIS WILAYAH RESAPAN DI LAMPUNG BARAT INVENTORY OF THE LOCAL KNOWLEDGE IN COFFEE AGROFORESTRY FOR SUSTAINABILITY DEBATE OF HYDRO-OROGICAL FUNCTION AT THE RECHARGE AREA IN WEST LAMPUNG - Nurhaida1, Ida ; Hariyanto, Sugeng Prayitno; Bakri, Samsul; Junaidi, Akmal; Syah, Pairul (Pembangunan Pedesaan, 2005)
Data base provided for a bottom-up development communication program and for given farmer voice in a debate of recharge area function sustainability at West Lampung, was conducted by inventory to local knowledge of agroforestry practices in August up to September 2004. Based upon the tribe dominant existed in the areas, four villages have been chosen as the area of study, i.e., Way Mengaku (Lampungese), Sukananti (Semendonese), Sidomakmur (Javanese), and Fajar Bulan (Sundanese). Four or five informants from 25 farmers visited have been founded in each village. The survey also intended to observe physical, socioeconomical and cultural characteristic. The main result achieved was 1) The Tao of local knowledge in the agroforestry practices needed to be affirmed was (a) seed selection, planting space for both coffee and shading trees, and multi-strata planting system exist in four tribes; (b) minimum tillage and litter basalt ground covering (Lampungese and Semendonese); (c) legume cover cropping (Javanese); (d) tuakh sakhak (Lampungese), kapak kulai (Semendonese), pungkak and stek of both tribes as the practices of coffee crop rejuvenation; (e) sheep, chicken, goose, duck poultry (Lampungese, Javanese, and Sundanese); and (f) fishery existed in Sudanese tribe. 2) The wrong practices in coffee agroforestry that need to be halted were (a) land clearing, cutting tree in the forest, slash and burn that existed in four tribes; (b) intensive soil tillage (Javanese); (c) litter basalt removing from land surface (Javanese). 3) The custom and the habituation found such as ngumbai (Lampungese), tunggu tumbang (Semendonese), and the custom in determination of planting event based on part of crop anatomy (Lampungese) or the star revolution (Semendonese) did not need to be halted.